Phase-Inserted Fiber Gratings and Their Applications to Optical Filtering, Optical Signal Processing, and Optical Sensing: Review - Chengliang Zhu; Lei Wang; Hongpu Li (Photonics, 2022)
Phase-inserted fiber gratings (PI-FGs) refer to those gratings where there exist a number of the phase-shifts (spatial spacing) among different sections (or local periods) of the gratings themselves. All the PI-FGs developed to date can mainly be divided into three categories: phase-shifted gratings, phase-only sampled gratings, and phase-modulated gratings, of which the utilized gratings could be either the Bragg ones (FBGs) or the long-period ones (LPGs). As results of the proposed the PI-FGs where the numbers, quantities, and positions of the inserted phases along the fiber direction are optimally selected, PI-FGs have already been designed and used as various complex filters such as the ultra-narrow filters, the triangular (edge) filters, the high channel-count filters, and the flat-top band-pass/band-stop filters, which, however, are extremely difficult or even impossible to be realized by using the ordinary fiber gratings. In this paper, we have briefly but fully reviewed the past and recent advances on PI-FGs, in which the principles and design methods, the corresponding fabrication techniques, and applications of the different PI-FGs to the fields of optical filtering, optical signal processing, and optical sensing, etc., have been highlighted.